Mechanistic studies and radiofluorination of structurally diverse pharmaceuticals with spirocyclic iodonium(iii) ylides. Issue 7 (4th April 2016) - Rotstein, Benjamin H.; Wang, Lu; Liu, Richard Y.; Patteson, Jon; Kwan, Eugene E.; Vasdev, Neil; Liang, Steven H.
Abstract : Theoretical studies provide insight into radiofluorination of non-activated electron-rich and sterically hindered 18 F-arenes using a new class of adamantyl-based spirocyclic iodonium(iii ) ylide precursors. Abstract : Synthesis of non-activated electron-rich and sterically hindered 18 F-arenes remains a major challenge due to limitations of existing radiofluorination methodologies. Herein, we report on our mechanistic investigations of spirocyclic iodonium(iii ) ylide precursors for arene radiofluorination, including their reactivity, selectivity, and stability with no-carrier-added [ 18 F]fluoride. Benchmark calculations at the G2[ECP] level indicate that pseudorotation and reductive elimination at iodine(iii ) can be modeled well by appropriately selected dispersion-corrected density functional methods. Modeling of the reaction pathways show that fluoride–iodonium(iii ) adduct intermediates are strongly activated and highly regioselective for reductive elimination of the desired [ 18 F]fluoroarenes (difference in barriers, ΔΔ G ‡ > 25 kcal mol −1 ). The advantage of spirocyclic auxiliaries is further supported by NMR spectroscopy studies, which bolster evidence for underlying decomposition processes which can be overcome for radiofluorination of iodonium(iii ) precursors. Using a novel adamantyl auxiliary, sterically hindered iodonium ylides have been developed to enable highly efficient radiofluorination of electron-rich arenes, including fragments of pharmaceutically relevant nitrogen-containing heterocycles and tertiary amines. Furthermore, this methodology has been applied for the syntheses of the radiopharmaceuticals 6-[ 18 F]fluoro- meta -tyrosine ([ 18 F]FMT, 11 ± 1% isolated radiochemical yield, non-decay-corrected (RCY, n.d.c.), n = 3), and meta -[ 18 F]fluorobenzylguanidine ([ 18 F]mFBG, 14 ± 1% isolated RCY, n.d.c., n = 3) which cannot be directly radiolabeled using conventional nucleophilic aromatic substitution with [ 18 F]fluoride.